Mineral processing design and operations : an introduction - Gupta, A.; Yan, D. S. (Elsevier, 2016)
Annotation "Mineral Processing Design and Operations: An Introduction, Second Edition," helps further understanding of the various methods commonly used in mineral beneficiation and concentration processes. Application of theory to practice is explained at each stage, helping operators understand associated implications in each unit process. Covers the theory and formulae for unit capacities and power requirements to help the designer develop the necessary equipment and flow-sheets to economically attain maximum yield and grade. This second edition describes theories and practices of design and operation of apparatus and equipment, including an additional chapter on magnetic, electrostatic, and conductivity modes of mineral separation. Basics of process controls for efficient and economic modes of separation are introduced. Outlines the theory and practice in the design of flow sheets and operation of an integrated mineral processing plantIntroduces the basic magnetism, electrostatic, conductivity, and dielectrophoresis properties of minerals and related separation techniquesDescribes automation in mineral processing plants allowing maximum yields and consistent high concentrate gradesOutlines problems and offers solutions in the form of various examples
Keywords: Ore-dressing.; elektronické knihy; electronic books